#### 2.236   ODE No. 236

$x (y(x)+4) y'(x)-y(x)^2-2 y(x)-2 x=0$ Mathematica : cpu = 0.12049 (sec), leaf count = 114

$\left \{\left \{y(x)\to -4+\frac {1}{x \left (\frac {1}{x^2+4 x}-\frac {e^{-2 \left (\frac {\log (x)}{4}+\frac {3}{4} \log (x+4)\right )}}{\sqrt {-\frac {4}{x+4}+c_1}}\right )}\right \},\left \{y(x)\to -4+\frac {1}{x \left (\frac {1}{x^2+4 x}+\frac {e^{-2 \left (\frac {\log (x)}{4}+\frac {3}{4} \log (x+4)\right )}}{\sqrt {-\frac {4}{x+4}+c_1}}\right )}\right \}\right \}$ Maple : cpu = 0.052 (sec), leaf count = 141

$\left \{ y \left ( x \right ) ={ \left ( - \left ( x+4 \right ) ^{{\frac {3}{2}}}\sqrt {{\frac {{\it \_C1}\, \left ( x+4 \right ) -4}{x+4}}}x-16\,\sqrt {x}-4\,{x}^{3/2} \right ) \left ( - \left ( x+4 \right ) ^{{\frac {3}{2}}}\sqrt {{\frac {{\it \_C1}\, \left ( x+4 \right ) -4}{x+4}}}+4\,\sqrt {x}+{x}^{{\frac {3}{2}}} \right ) ^{-1}},y \left ( x \right ) ={ \left ( \left ( x+4 \right ) ^{{\frac {3}{2}}}\sqrt {{\frac {{\it \_C1}\, \left ( x+4 \right ) -4}{x+4}}}x-16\,\sqrt {x}-4\,{x}^{3/2} \right ) \left ( \left ( x+4 \right ) ^{{\frac {3}{2}}}\sqrt {{\frac {{\it \_C1}\, \left ( x+4 \right ) -4}{x+4}}}+4\,\sqrt {x}+{x}^{{\frac {3}{2}}} \right ) ^{-1}} \right \}$